Hospital information systems implementation framework: critical success factors for Malaysian public hospitals - Abdullah, Zainatul Shima (Curtin University, 2013)
The delivery of high quality health services is among the most important government policies in healthcare; it is demonstrated via the significant investment committed to expand the sector. In order to provide quality health services, Hospital Information Systems (HIS) development and adoption has to be initiated; though evidence has shown that implementing HIS is not easy. To ensure continuous successful implementation, the understanding and determination of HIS implementation factors has become a crucial consideration for health providers. This study, instigated to alleviate this problem, identified critical factors that influence HIS implementation and examined structured indicators to measure HIS implementation.Based on the critical success factors (CSFs) and DeLone and McLean’s Information Systems success model, the research study developed an implementation framework comprised of essential elements to guide HIS implementation. In the framework, the DeLone and McLean IS success measures were adapted and presented as a reflective second order factor to capture the multifaceted nature of success. A total of 500 questionnaires were distributed to six public hospitals in Malaysia and 213 were used for analysis. This reflects a high response rate of 42.6 percent. To evaluate the extent of success, the partial least squares (PLS) based structural equation modeling (SEM) approach was employed. The findings of the study revealed that the CSFs in Malaysia differ from studies in developed countries. Three out of seven success factors namely system selection, enterprise-wide communication and team composition proved to be significant. Key implementation factors such as top management support, business planning, project management and change management were found to be insignificant.The study is among the few that have tested empirically an implementation framework in the Malaysian settings; as such, it contributes significantly to theoretical, methodological and practical aspects of research. Theoretically, it established a new classification of CSFs that could influence HIS implementation. This new categorization is a significant effort to provide a practical list of CSFs that allows practitioners to focus on key areas during system implementation.Additionally, the study presents a new model that suggests links or correlations between the CSFs and how these factors should be implemented.With regard to research methodology, the study collected data from Malaysian public hospitals having a Total Hospital Information System (THIS) implementation; the type of data is rare considering the complex procedures involved. Also, the quantitative approach employed is suitable to attest the effectiveness of the implementation model. This study also utilized the SEM component-based or PLS analysis for assessing the implementation model. At present, it is still uncommon to find HIS implementation studies that utilize PLS analysis in Malaysia.In terms of a practical contribution, the study provides guidelines for managers in decision-making and planning future HIS implementation. The risks of failures for HIS implementation could be reduced as the study also proposed the approach on how the CSFs should be implemented. Most importantly, this study has established a model that could assists practitioners and researchers in understanding the implementation process of HIS, specifically for Malaysian public hospitals. Additionally, its contribution can be used in analogous domains such as information systems (IS), enterprise resource planning (ERP) and enterprise systems (ES).